2019
DOI: 10.1111/ina.12528
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of decabromodiphenyl ether and emerging brominated flame retardants in dust, air and window surfaces of newly built low‐energy preschools

Abstract: The envelope of low‐energy buildings is generally constructed with significant amounts of plastics, sealants and insulation materials that are known to contain various chemical additives to improve specific functionalities. A commonly used group of additives are flame retardants to prevent the spread of fire. In this study, decabromodiphenyl ether (BDE‐209) and fourteen emerging brominated flame retardants (BFRs) were analyzed in indoor dust, air and on the window surface of newly built low‐energy preschools t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
5
2
Order By: Relevance
“…Highest median concentrations were detected in schools (10,000 ng/g), followed by cars (7,700 ng/g), offices (6,100 ng/g) and homes (4,200 ng/g). Concentration data exceed markedly those reported for similar microenvironments across Europe, China and Australia [45][46][47][48] .…”
Section: Dbdpecontrasting
confidence: 83%
See 2 more Smart Citations
“…Highest median concentrations were detected in schools (10,000 ng/g), followed by cars (7,700 ng/g), offices (6,100 ng/g) and homes (4,200 ng/g). Concentration data exceed markedly those reported for similar microenvironments across Europe, China and Australia [45][46][47][48] .…”
Section: Dbdpecontrasting
confidence: 83%
“…Median DBDPE concentrations reported for Irish cars also exceed those in Greece 54 , while those in Irish offices exceed those in Australia 48 . Moreover, median concentrations in Irish schools exceed those recently reported for low energy Swedish preschools (300 times higher) 55 and preschools in Stockholm (100 times higher) 46 . In agreement with other international studies, BDE-209 was the most abundant PBDE congener detected across all microenvironments 28,32,33 , contributing to >99% of SPBDEs for homes, cars and schools, and 98% in offices.…”
Section: Dbdpecontrasting
confidence: 56%
See 1 more Smart Citation
“…A Swedish study showed that concentrations of several groups of hazardous chemicals in preschool dust decreased between 2 and 60% after implementation of the article substitution action in preschools 45 . OPEs and selected BFRs decreased in air and dust in preschools built with approved building materials, compared to a preschool constructed using conventional materials 39,42 . The present study is in agreement with these published intervention studies, and it is the first study that focused on comparing different measures to phase out several groups of hazardous SVOCs from the preschools’ indoor environment.…”
Section: Discussionsupporting
confidence: 89%
“…In Sweden, a few studies have similarly found phthalates and alternative plasticizers, 37,38 OPEs 39 PBDEs, HBCD and in some cases, new BFRs 40–42 as well as bisphenols 38 in air and/or dust in preschools.…”
Section: Introductionmentioning
confidence: 99%